The dynamics of exploitation and class in accumulation economies - Jonathan F. Cogliano; Roberto Veneziani; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2014)
This paper analyses the equilibrium dynamics of exploitation and class in general accumulation economies with population growth, technical change, and bargaining by adopting a novel computational approach. First, the determinants of the emergence and persistence of exploitation and class are investigated, and the role of labour-saving technical change and, even more importantly, power is highlighted. Second, it is shown that the concept of exploitation provides the foundations for a logically coherent and empirically relevant analysis of inequalities and class relations in advanced capitalist economies. An index that identifies the exploitation level, or intensity of each individual can be defined and its empirical distribution studied using the standard tools developed in the theory of inequality measurement.
Keywords: B51; D63; C63; 330; Exploitation; class; accumulation; simulation